Bukovniki, cenzura in Drabosnjak, "poredni paur" iz Korotana - Dović, Marijan (Slavistična revija, 2022)
This article deals with the literary work of the Carinthian folk poet and writer Andrej Šuster – Drabosnjak (1768–1825) and his conflict with the authorities at the beginning of the nineteenth century, which severely affected him both materially and creatively. The analysis shows that Drabosnjak may have been problematic because he translated and distributed forbidden or undesirable books, and that individual critical passages in his illegally printed brochures Svovenji obace and Latania may have been particularly controversial.
Keywords: Carinthia; cesarska cenzura; Habsburg monarchy; habsburška monarhija; imperial censorship; Koroška; parodija; parody; satira; satire; Slovene literature; slovenks književnost; Šuster, Andrej